Microgrippers: A Monolithic Force‐Sensitive 3D Microgripper Fabricated on the Tip of an Optical Fiber Using 2‐Photon Polymerization (Small 16/2018). Issue 16 (19th April 2018) - Power, Maura; Thompson, Alex J.; Anastasova, Salzitsa; Yang, Guang‐Zhong
Abstract : In article number1703964, Guang‐Zhong Yang and co‐workers use light from a single mode optical fiber to interrogate the integrated sensor of a compliant microgripper. An applied force results in the spacing of the thin‐layer features to change and, hence, vary the interference pattern. The spectrum of the light reflected back along the fiber can then be used to determine applied force.